Glottalisations in today's London English - Ježek, Miroslav (2006)
Against the background of phonetic and sociolinguistic studies of glottalisations in London/Estuary English made so far, this thesis is an analysis of the pronunciation of five speakers from London based on recordings and their transcriptions. Statistical distributions are offered, as well as phonetic and sociolinguistic conclusions